Analisis Getaran Pada Footrest Sepeda Motor Tipe Matic dan Non-Matic - Rokhman, Taufiqur (Jurnal Ilmiah Teknik Mesin, 2016)
Vibration that occurs in a device or instrument that we use often cause discomfort. Not only that, excessive vibration on the device sooner or later will cause damage to the system components. Therefore, it is important to detect vibration and subsequent attempt is made to minimize vibrations that occur so that comfort can be achieved and the damage can be minimized or even eliminated. The purpose of this study was to determine the vibration occurs in the type of motorcycle footrest matic and non-matic. In addition, knowing the extent to which differences in vibrations that occur in the type of motorcycle footrest matic and non-matic. The method used in this study is the method of testing of materials (objects) which in this case are two types of motorcycle matic and non-matic using test equipment (Accelerometer). In the non-motorcycle footrest matic vibration, characteristics are obtained farthest deviation (amplitude) in each direction of the x, y and z are respectively 2, 741 cm, 1.882 cm and 1.415 cm. The average speed in each direction of the x, y and z are respectively 2.908 cm / s, 1.893 cm / s, and 1.204 cm / s. And for the average acceleration in each direction of the x, y and z are respectively 1.701 cm /s2, 1.146 cm/s2 and 0.663 cm / s2. While footrest matic motorcycle derived vibration characteristics is that the farthest deviation (amplitude) in each direction of the x, y, and z respectively amounted to 1.590 cm, 0.826 cm and 1.268 cm. The average speed in each direction of the x, y and z are respectively 1.077 cm / s, 0.5301 cm / s, and 0.6343 cm / s. And for the average acceleration in each direction of the x, y and z are respectively 0.8627 cm /s2, 0.3747 cm / s2, and 0.3993 cm / s2